Kreativitas Iklan Lewat Tiktok dan Pengaruhnya terhadap Keputusan Berinvestasi - Figar Alif Gifari; Oktaviana Purnamasari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Creative elements in advertising are needed to make advertisements different from one advertisement to another. The purpose of this study is to measure advertising creativity on investment decisions. and how much influence they exert. The theory used in this study is the theory of Advertising Creativity which includes advertising relevance, advertising theme, message appeal and advertising model as well as the theory of Purchase Decision which includes problem recognition, information search, evaluation of alternatives, purchase decisions, and post-purchase behavior. This study uses a quantitative approach and survey research methods. The data collection technique was carried out by distributing questionnaires to 76 predetermined respondents. Sampling using the Simple Random Sampling Technique (Lottery Technique). This research is shown by the average value of respondents' answers to variable (X) of 3.188, this value is classified as high (Agree) and the average respondent's answer to variable (Y) is also classified as high (Agree) of 3.172. The considerable influence of advertising creativity and purchasing decisions can also be seen in the correlation (R) value of 0.711 which is quite high and the R square value of 0.505 or 50.5% has an effect while the remaining 49.5% is influenced by other factors.